Pentagon Fraud and Financial Statement Fraud in State-Owned Enterprises Listed on the Indonesia Stock Exchange During 2021–2025: The Moderating Role of the Audit Committee - Hidayat Darwis; Supriatiningsih Supriatiningsih; Samukri Samukri (Ilomata International Journal of Tax and Accounting, 2026)
This study seeks to examine the impact of the Fraud Pentagon factors pressure, opportunity, rationalization, competence, and arrogance on financial statement fraud within Indonesian State-Owned Enterprises (SOEs), while also investigating the moderating influence of the audit committee on this relationship. The research used a quantitative methodology, analyzing panel data from 16 state owned enterprises listed on the IDX from 2021 to 2025, yielding 80 balanced panel observations. Panel regression analysis was performed, using the FEM as determined by the Chow and Hausman tests. Financial statement fraud was assessed using the F-Score model, while the audit committee was evaluated as a moderating variable via MRA. The findings indicate that pressure, opportunity, and arrogance positively and significantly influence financial statement fraud, whereas rationalization and competence do not. Regarding the moderating role of the audit committee, the results show that the audit committee significantly weakens the relationship between opportunity and financial statement fraud at the 5 percent significance level. Meanwhile, the moderating effects on the relationships between pressure and financial statement fraud and between arrogance and financial statement fraud are only marginally significant at the 10 percent significance level. No significant moderating effects were found for rationalization and competence. This study contributes to the development of Fraud Pentagon Theory and Agency Theory by emphasizing the importance of monitoring effectiveness in preventing fraudulent financial reporting in SOEs.